High frequency abrupt shifts in the Indian summer monsoon since Younger Dryas in the Himalaya - Ali, Sheikh Nawaz (Sci Rep, 2018)
In order to quantify the Indian summer monsoon (ISM) variability for a monsoon dominated agrarian based Indian socio-economy, we used combined high resolution δ(13)C, total organic carbon (TOC), sediment texture and environmental magnetic data of the samples from a ~3 m deep glacial outwash sedimentary profile from the Sikkim Himalaya. Our decadal to centennial scale records identified five positive and three negative excursions of the ISM since last ~13 ka. The most prominent abrupt negative ISM shift was observed during the termination of the Younger Dryas (YD) between ~11.7 and 11.4 ka. While, ISM was stable between ~11 and 6 ka, and declined prominently between 6 and 3 ka. Surprisingly, during both the Medieval Warm Period (MWP) and Little Ice age (LIA) spans, ISM was strong in this part of the Himalaya. These regional changes in ISM were coupled to southward shifting in mean position of the Intertropical Convergence Zone (ITCZ) and variations in East Asian monsoon (EAM). Our rainfall reconstructions are broadly in agreement with local, regional reconstructions and PMIP3, CSIRO-MK3L model simulations.